Chemical basis of combination therapy to combat antibiotic resistance - Si, Zhangyong (2023)
The antimicrobial resistance crisis is a global health issue requiring discovery and development of novel therapeutics. However, conventional screening of natural products or synthetic chemical libraries is uncertain. Combination therapy using approved antibiotics with inhibitors targeting innate resistance mechanisms provides an alternative strategy to develop potent therapeutics. This review discusses the chemical structures of effective β-lactamase inhibitors, outer membrane permeabilizers, and efflux pump inhibitors that act as adjuvant molecules of classical antibiotics. Rational design of the chemical structures of adjuvants will provide methods to impart or restore efficacy to classical antibiotics for inherently antibiotic-resistant bacteria. As many bacteria have multiple resistance pathways, adjuvant molecules simultaneously targeting multiple pathways are promising approaches to combat multi-drug-resistant bacterial infections.